Psychometric Properties of the Persian Version of the Spiritual Well-Being Scale Among Iranian Potential Organ Donors - Sharif-Nia, Hamid (Journal of religion and health, 2023)
The Spiritual Well-Being Scale (SWBS) is a widely used scale that requires evaluation for the Iranian population. This study aimed to determine the psychometric properties of the SWBS among a sample of potential Iranian organ donors. The research was conducted in 2022 in Iran using cross-sectional methodological design. The sample consisted of 316 individuals from the Iranian community who expressed willingness to donate organs. Convenience sampling was used to select the participants. The construct validity and reliability of the Persian version of the SWBS were assessed. The results from maximum likelihood (ML) and confirmatory factor analysis (CFA) revealed three factors labeled as higher power, the meaning of life, and the purpose of life, which explained 50.2% of the total variance in the concept of Spiritual Well-Being (SWB). The results indicated that the model was appropriate. Cronbach's Alpha and McDonald's Omega demonstrated an acceptable internal consistency of the scale. All the statistical analyses were performed using SPSS 27 and AMOS 27 software. These findings suggest that the Persian version of the SWBS is a reliable and valid scale for assessing the spiritual well-being of individuals who are willing to donate organs. The scale comprises 16 items related to higher power, meaning of life, and sense of life.